Pembuatan Pestisida Nabati Menggunakan Metode Ekstraksi Dari Kulit Jengkol Dan Umibi Bawang Putih - Ifni Rimijuna; Elvi Yenie; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The use of botanical pesticides is one alternative that is safe and environmentally friendly to take advantage of the potential of plant extracts as pesticides to control pests. The purpose of this research is to making of botanical pesticides from leather jiringa and garlic, test secondary metabolites component of maximum yield. The research was done by extraction method, and separation of secondary metabolites with rotary evaporator with a variation of submersion that is 3, 5, 7, 9, and 11 days, the ratio of material and solvent is 1: 4. The highest result is secondary metabolites components successfully tested are alkaloids, flavonoids, tannins, saponins, and sulfur.Keywords: Botanical pesticides, extraction, leather jiringa, garlics, LC50